PERSEPSI MASYARAKAT TERHADAP PERTUNJUKAN KRINOK PADA ACARA PESTA PERKAWINAN DI KABUPATEN BUNGO - Gusti Rahayu; Marzam Marzam; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2012)
This Research was aimed at finding and describing community’s perception towards the Krinok performances in wedding receptions at village Rantau Embacang in Bungo Regency. The perception was viewed from the perspectives of four community elements, i.e. audience, players, function organizers, and community figures. Data Collection was performed through observation, interviews, documentation, and library research. The result of The Research indicated that Krinok performances at wedding receptions in village Rantau Embacang were an entertaining art, containing communicative quatrain poems. Krinok was in possession of typical rhythm and melody; the sound and the lyrics of Krinok chant conveyed certain meanings for the locals. Krinok reflected community’s social values, an art that united the community and revealed teachings or guidance in life through its lyrics. Keywords: Community Perception, Krinok Performances